Effectiveness Of Various Active Ingredients In Controlling Anthracnose Fungi In Post-Harvest Mango (Mangifera Indica L.) - Riyadl Izzur Rohman; Wiharyanti Nur Lailiyah; Suhaili ‎; Adiet Cantyo Pamungkas (UNIVED Press, Dehasen University Bengkulu, 2025)
The Purpose : This study aimed to evaluate the effectiveness of various active ingredients in controlling anthracnose (Colletotrichum gloeosporioides) on postharvest mangoes (Mangifera indica L.). Anthracnose is a key postharvest disease that affects fruit quality and shelf life. Methodology : A Completely Randomized Design (CRD) was applied with five treatments : control, azoxystrobin + difenoconazole, mancozeb 75%, mancozeb + carbendazim, and propineb 70%, each replicated five times. Parameters included time of fungal emergence and the extent of fungal spread during storage. Results : The combination of azoxystrobin and difenoconazole significantly delayed fungal emergence to an average of 7.4 days and reduced the spread score to 1.8 on a 1–5 scale. Findings : This treatment exhibited superior efficacy compared to others, highlighting the synergistic effect of dual-action fungicides. Novelty : The research introduces the use of dual-mode fungicide combinations as a novel approach for postharvest disease management in mangoes. Originality : This study presents original data supporting the use of specific active ingredient combinations, offering new perspectives for enhancing fruit preservation. Conclusion: Azoxystrobin and difenoconazole were most effective in suppressing anthracnose, providing a practical strategy for extending mango shelf life and maintaining quality. Type of Paper : Empirical Research Aricle.